Collaborative and Cooperative Learning Innovation for Islamic Religious Education Subjects at Madrasah Diniyah Takmiliyah Ula Al Ikhlas Madura - Nur Jihan Nabilah; Dian Nurkholila; Dina Mardiana (Tinta Emas Institute, 2025)
This study aims to analyze and describe collaborative and cooperative learning innovations in improving students' understanding of Islamic Religious Education (PAI) subjects at Madrasah Diniyah Takmiliyah (MDT) Ula Al-Ikhlas Madura. The background of this research is based on initial observations that the Islamic Religious Education learning process at MDT Ula Al-Ikhlas Madura still uses conventional methods that are one-way and emphasize cognitive aspects only, thus providing less space for students to think critically and interact actively. The method in this research uses a qualitative approach with a descriptive type which aims to obtain an in-depth, systematic, and factual picture regarding the application of collaborative and cooperative learning innovations in PAI subjects at MDT Ula Al-Ikhlas Madura. Data was collected through observation techniques, in-depth interviews, and documentation of Islamic Education teachers and students at MDT Ula Al-Ikhlas Madura. Data analysis is carried out through data reduction, data presentation, and drawing conclusions. The results of this study indicate that the implementation of collaborative and cooperative learning models can create an active, interactive learning environment among students. This learning innovation encourages students to think critically, work collaboratively in groups, and better understand Islamic values ​​through direct learning experiences. The increase in students' understanding can be seen from their involvement in discussions, their ability to explain the concepts of Islamic teachings, and changes in behavior in daily worship practices.